Differential regulation of sorbitol and sucrose loading into the phloem of Plantago major in response to salt stress. - Pommerrenig, Benjamin; Stal Papini, Flavia; Sauer, Norbert (Plant Physiology, 2007)
Several plant families generate polyols, the reduced form of monosaccharides, as one of their primary photosynthetic products. Together with sucrose (Suc) or raffinose, these polyols are used for long-distance allocation of photosynthetically fixed carbon in the phloem. Many species from these families accumulate these polyols under salt or drought stress, and the underlying regulation of polyol biosynthetic or oxidizing enzymes has been studied in detail. Here, we present results on the differential regulation of genes that encode transport proteins involved in phloem loading with sorbitol and Suc under salt stress. In the Suc- and sorbitol-translocating species Plantago major, the mRNA levels of the vascular sorbitol transporters PmPLT1 and PmPLT2 are rapidly up-regulated in response to salt treatment. In contrast, mRNA levels for the phloem Suc transporter PmSUC2 stay constant during the initial phase of salt treatment and are down-regulated after 24 h of salt stress. This adaptation in phloem loading is paralleled by a down-regulation of mRNA levels for a predicted sorbitol dehydrogenase (PmSDH1) in the entire leaf and of mRNA levels for a predicted Suc phosphate synthase (PmSPS1) in the vasculature. Analyses of Suc and sorbitol concentrations in leaves, in enriched vascular tissue, and in phloem exudates of detached leaves revealed an accumulation of sorbitol and, to a lesser extent, of Suc within the leaves of salt-stressed plants, a reduced rate of phloem sap exudation after NaCl treatment, and an increased sorbitol-to-Suc ratio within the phloem sap. Thus, the up-regulation of PmPLT1 and PmPLT2 expression upon salt stress results in a preferred loading of sorbitol into the phloem of P. major.